Policy versus reality within the African anti-human trafficking architecture : The case of Kenyan domestic workers in modern slavery in Saudi Arabia - Wahu, Milka; Kaime, Thoko (Intractable Problems of Human Rights, 2025)
The problem of human trafficking in Kenya remains deeply entrenched. Although multiple regulatory efforts have been adopted to rein in this challenge, it rages on with the recent reports projecting its increase. As a result, the discrepancy between policy and realities and lived human trafficking experiences of domestic workers using the Kenya-Saudi Arabia route is not only glaring but also one that deserves scholarly attention, especially considering recent experiences. This chapter has examined the gap between the policy positions, including emerging and recent ones, and the reality of combating human trafficking. Using mixed methods consisting of doctrinal evaluation of the law and reports, and also interviews, the authors have explored the nature and extent of this discrepancy. The chapter makes a finding that the legal, regulatory and administrative efforts for ensuring the welfare of domestic workers in Saudi Arabia, who are victims of human trafficking and modern slavery, have yet to fully and effectively address the challenge. To address the practical realities that cause or exacerbate this challenge, moving forward, the chapter recommends that the Kenyan government prioritise the ratification of certain treaty laws, demonstrate political goodwill through the implementation of parliamentary reports on the challenge, prioritise the human rights approach to the regulation of aspects of human trafficking, and provide meaningful financial and legal backing to the institutions tasked with combating human trafficking in Kenya.